PERANAN STRATEGIC LEADERSHIP TERHADAP COMPETITIVE POSITIONING MELALUI ORGANIZATION LEARNING STUDY KASUS PADA PERUSAHAAN MANUFAKTUR DI SURABAYA - Jessica Kosasih (Business Accounting Review, 2015)
This study was intended to know how the role of strategic leadership to the competitive positioning of the manufacturing company in Surabaya, as well as in addition to know how the role of strategic leadership to the competitive positioning through the organization learning manufacturing company in Surabaya. In this study, the data collected by distributing questionnaires to 30 manufacturing companies in Surabaya and each company used the 2-3 respondents. This research usied Structural Equation Model analysis of Partial Least Square software. The survey results revealed that the strategic leadership had positive influence on competitive positioning and organization learning did not reinforce a positive influence on the competitive positioning of strategic leadership.